Granzyme B and melittin in cancer immunotherapy: molecular mechanisms and therapeutic perspectives in head and neck cancers - Majchrzak, Adam; Lewandowski, Filip; Hrynkiewicz, Rafał; Poniewierska-Baran, Agata; Bębnowska, Dominika; Niedźwiedzka-Rystwej, Paulina (Frontiers in Immunology, 2025)
Granzyme B (GZMB) and melittin are potent cytotoxic agents with promising applications in cancer immunotherapy, particularly in head and neck squamous cell carcinoma (HNSC). GZMB, secreted by cytotoxic T lymphocytes and natural killer (NK) cells, induces apoptosis through caspase activation and mitochondrial disruption. Its expression in HNSC correlates with both improved prognosis and, paradoxically, immune suppression via regulatory T cells. Melittin, a peptide derived from bee venom, exerts anticancer effects by disrupting cancer cell membranes, inducing oxidative stress, and activating apoptotic pathways. While effective, its non-specific cytotoxicity poses a therapeutic challenge, which is being addressed through targeted delivery systems, such as nanoparticles and liposomes. This review highlights the distinct yet potentially complementary roles of GZMB and melittin in modulating tumor cell death and the tumor microenvironment. We also discuss mechanisms of resistance, including expression of granzyme inhibitors (e.g., PI-9), altered membrane dynamics, and G2/M cell cycle arrest. Combining the specificity of immune-mediated GZMB action with the broad cytotoxicity of melittin may offer synergistic benefits in future therapies. Understanding these molecules’ mechanisms provides a foundation for novel immunotherapeutic strategies in the treatment of HNSC and other solid tumor.